The Quest for Identity of Health Informatics and for Guidance to Education in it – The German Reisensburg Conference of 1973 Revisited - Moehr, J.R. (Yearbook of Medical Informatics, 2004)
Purpose: To review the minutes of the invitational workshop for defining the contents and approaches to education in and the professionalization of health informatics, which took place in Germany thirty years ago; To provide context for the meeting and assess its impact.Approach: The minutes resulting from the meeting were translated into English, and the literature attesting to the effects of the meeting was compiled in a literature review and commented on.Results: The meeting had profound effect in Germany, providing a model for several tiers of educational initiatives, and for professional recognition of the field of medical informatics. These were refined over the last thirty years and persist to this day. At the international level, the impact can be traced to the IMIA recommendations for education in health/medical informatics. More recent initiatives at defining the content of health informatics education did not result in fundamentally different models.Conclusion: One may assume then that the contents of education in medical/health informatics are well defined. The methods of education deserve greater attention.